Application of Chain Writing Method to Improve Short Story Writing Skills in Grade VIII Students of SMP Negeri 16 Cimahi - Ichsan Nuralam; Wikanengsih; Rochmat Tri Sudrajat (JLER (Journal of Language Education Research), 2024)
This research aims to reveal the improvement in learning outcomes of short story texts using picture story books in class VIII students at SMP Negeri 16 Cimahi. The problem of this research is related to the use of the chain writing method in learning short story texts in class VIII of SMP Negeri 16 Cimahi. The research method used in this research is PTK (Classroom Action Research) or CAR (Classroom Action Research). Classroom Action Research is carried out in four stages, namely planning, implementing actions, observing and reflecting. This research was carried out at FFF Middle School, data collection techniques were carried out through direct observation in the classroom while teaching and learning activities were taking place. The results of the research show that there is an increase in student learning outcomes in learning short story texts using the chain fifth method. This is shown by an increase in the number of 31 students who took part in cycle I and cycle II. Each cycle experiences an increase in the pretest and posttest results. The increase in cycle I reached 19.35% and the increase in cycle II reached 51.3%. This increase made the writer feel that it was sufficient so that he did not continue with cycle III. In this way, the author concludes that picture story book media can improve the activities and learning outcomes of class VIII students at SMP Negeri 16 Cimahi.